Surgical tool motion during conventional freehand and robot-assisted microsurgery conducted using neuroArm. (2nd May 2016) - Maddahi, Yaser; Zareinia, Kourosh; Sepehri, Nariman; Sutherland, Garnette
Abstract: Surgical tool motion during microsurgery could arguably reflect surgical performance. This paper reports on how the motion of a surgical tool correlates or differs between conventional freehand surgery and robot-assisted surgery. In this pilot study, components of the position and orientation as well as the linear and angular velocities of a surgical tool, over the same period of operation, are compared during the two scenarios. For freehand surgery, a bipolar forceps is retrofitted with a tracking system to measure translational and rotational components of the tool motion. In robot-assisted surgery, the position and orientation components are obtained using kinematics of the neuroArm image-guided robotic system. A cross correlation analysis was used to investigate correlation between each pair of displacement or velocity components from freehand and robot-assisted scenarios to indicate how strongly or weakly two sets of data are linked together. The absolute maximum value of the cross correlation coefficient is calculated for each pair of components to quantitatively investigate the correlation between two sets of data. Results showed that the positional and rotational components, reflecting the surgical workspace, in both scenarios are correlated. However, for the cases studied, surgical tool rate of motion differs between the two scenarios. Results are important as they can be utilized to design robot-assisted neurosurgical systems that reflect characteristics of freehand surgery gained by surgeons through years of training, knowledge, and experience. Graphical Abstract: